2021
DOI: 10.3390/cancers13112777
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA in Pancreatic Cancer Diagnosis, Prognosis, and Treatment: From Bench to Bedside

Abstract: Pancreatic cancer is the fourth leading cause of cancer death among men and women in the United States, and pancreatic ductal adenocarcinoma (PDAC) accounts for more than 90% of pancreatic cancer cases. PDAC is one of the most lethal gastrointestinal malignancies with an overall five-year survival rate of ~10%. Developing effective therapeutic strategies against pancreatic cancer is a great challenge. Novel diagnostic, prognostic, and therapeutic strategies are an immediate necessity to increase the survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 190 publications
(250 reference statements)
0
15
0
Order By: Relevance
“…MiRNA has its specific expression spectrum, and it is reported that extracellular miRNAs can circulate in the bloodstream being remarkably stable [2]. They have been studied as markers of many diseases since its discovery, mostly in cancers like pancreatic cancer and breast cancer [3][4][5]. In recent years, several literatures have reported that microRNA-146 (miR-146) may play an important role in the pathological process of RA and may be a diagnostic marker of RA.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA has its specific expression spectrum, and it is reported that extracellular miRNAs can circulate in the bloodstream being remarkably stable [2]. They have been studied as markers of many diseases since its discovery, mostly in cancers like pancreatic cancer and breast cancer [3][4][5]. In recent years, several literatures have reported that microRNA-146 (miR-146) may play an important role in the pathological process of RA and may be a diagnostic marker of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, circulating exosomal miRNAs have been proposed as predictive and prognostic biomarkers in cancer [41,42,58]. In the context of pancreatic cancer, multiple functional analyses have confirmed the significant role that exosomal miR-NAs play in tumour cells-CAFs crosstalk, PDAC pathogenesis, diagnosis, and response to therapy [11,12,43,81,100,117]. Pancreatic cancer is highly metastatic, with liver the most common site of distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, we showed that the expression levels of miR-155 were significantly increased, when PDAC cells were exposed to NiCl2 compared with the control Panc-1 and MiaPaCa-2 cells. A recent study has also mentioned that numerous exosomal miRs such as miR-155, could be potential biomarkers for the early diagnosis of this malignancy [ 109 ], while further studies have shown that miR-155 is linked to clinical stage and lymph node metastasis in PDAC patients [ 110 , 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%